2012
DOI: 10.1093/abbs/gms013
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by casticin in cervical cancer cells: reactive oxygen species-dependent sustained activation of Jun N-terminal kinase

Abstract: Casticin, a polymethoxyflavone from Fructus viticis used as an anti-inflammatory agent in Chinese traditional medicine, has been reported to have anti-cancer activity. The purpose of this study was to examine the apoptotic activity of casticin on human cervical cancer cells and its molecular mechanism. We revealed a novel mechanism by which casticin-induced apoptosis occurs and showed for the first time that the apoptosis induced by casticin is mediated through generation of reactive oxygen species (ROS) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 36 publications
(42 reference statements)
4
41
0
Order By: Relevance
“…Because excessive ROS production can induce depolarization of MMP, next we performed flow cytometric analysis to determine MMP in control and vitexicarpin-treated cells. The data showed that MMP in vitexicarpin-treated PC-3 cells was significantly decreased which is in line well with previous result found in Hela cells (Chen et al, 2011;Zeng et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Because excessive ROS production can induce depolarization of MMP, next we performed flow cytometric analysis to determine MMP in control and vitexicarpin-treated cells. The data showed that MMP in vitexicarpin-treated PC-3 cells was significantly decreased which is in line well with previous result found in Hela cells (Chen et al, 2011;Zeng et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…It showed that vitexicarpin dosedependently induced apoptosis in PC-3 cells. Previous studies have indicated that vitexicarpin induced apoptosis in hepatocellular carcinoma HepG2 (Yang et al, 2011;He et al, 2012) and human cervical cancer cells (Chen et al, 2011;Zeng et al, 2012). Also, we found vitexicarpin induced apoptotic cell death in PC-3 cells in a dosedependent manner.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Vitexicarpinis reported to induce growth inhibition, cell cycle arrest, and apoptosis in human cervical cancer cell line HeLa (Chen et al, 2011;Zeng et al, 2012), hepato-…”
Section: Introductionmentioning
confidence: 99%